Identifying Potential Child Abuse through Oral Examination. (2nd April 2017) - Printz, Jillian N.; Baker, Aaron; Carr, Michele
Abstract : Limited reports of oropharyngeal trauma exist in the literature even though this type of injury is extremely common in pediatric populations. There are no widely agreed upon diagnostic and management tools for such injuries in abuse cases, emphasizing the importance of reporting rare cases of orofacial trauma. This case report of a soft palate laceration demonstrates an instance of initially unrecognized potential child abuse. We aim to clarify understanding of such injuries. Furthermore, the report highlights the need for recognition of oral signs of child abuse in order to promote early detection, reporting, and appropriate management.